Answer:
9x^4-25x^2+16
Step-by-step explanation:
(x^2−1)(3x−4)(3x+4)=(*)
(x^2−1)((3x)^2−4^2) =
(x^2 - 1)(9x^2-16)=
x^2*9x^2 - x^2*16 - 1*9x^2 +16=
9x^4-16x^2-9x^2+16=
9x^4-25x^2+16
(*) (A-B)(A+B) =A^2 - B^2
Do you still need help with this if so graphes have a bigger letter and a smaller letter
Answer:
Only the given table represents a function. Option 1 is correct.
Step-by-step explanation:
A relation is called a function, if there exist a unique value of y for each value of x. It means for each input there exist a unique output.
A function is always a relation but all relations are not function.
In the given table for each value of x, we have unique value of y, therefore the given table represents a function.
In second relation, at x=-2, the values of y are y=10 and y=-7. For single x, there are more than one value of y, therefore the second relation is not a function.
In third relation, at x=6, the values of y are y=-2 and y=1. For single x, there are more than one value of y, therefore the third relation is not a function.
Change the equation to slope intercept form:
-5y=-x+10
y=1/5x-2
The y intercept is -2